CompTIA Cloud+ CV0-001 : complete video course - Dulaney, Emmett A. (LiveLessons (Indianapolis, Ind.), 2014)
CompTIA Cloud+ LiveLessons is a unique video product that provides a solid understanding of cloud-based technologies and infrastructure. It looks at server, network, storage, and virtualization technologies and the aspects of IT security needed to implement industry best practices and pass the CompTIA Cloud+ certification exam. The product takes the student from an introduction to the fundamental concepts to a reasonably sophisticated understanding of the topics. Each lesson includes a summary with interactive exercises so you can review the material and then quiz yourself on the knowledge you’ve learned. CompTIA Cloud+ LiveLessons contains 7 individual video lessons, subdivided into 32 sublessons. The videos consist of audio instruction, animations, and video screencasts. Each video lab presents detailed objectives, lab diagrams, and video captures. Audio instruction throughout offers detailed explanations, tips, and configuration verifications. A lesson review and lesson quizzes are also included so you can test yourself on the information learned.